STUDI PARAMETER OSEANOGRAFI FISIK PERAIRAN PULAU DERAWAN - Roem, Muhamad; Laga, Asbar; Listina, Ika; Rukmana, Indrawati; Astriani, Kiki (Jurnal Harpodon Borneo, 2016)
A study on waves, tides and tidal currents has been done to understanding the oceanography characters  of  Derawan Island.  Wave  modeling done  by the approach hindcasting methods. Derawan tidal was analyzed with admiralty method to determine the tidal constituent. Tidal currents has been studied with the plot stick approach. In general, our results show that the largest waves probability come from the northeast with a wave height between 1-4 m. Derawan tidal type are mixed with the meanseal level values at 224 cm. Key words : Derawan, Oseanography, Wave, Tidal Current.